Social Pedagogy in South Africa: holding the tension between academia and activism - Astrid Von Kotze; Salma Ismail; Linda Cooper (Pedagogía Social: Revista Interuniversitaria, 2015)
‘Social pedagogy’ is not a familiar term in South Africa. Instead, everything to do with education outside or beyond schooling is subsumed under ‘adult education’. Community education or alterna- tives are generally known as ‘radical’ or ‘popular’ education’ concerned with social, economic and political transformation. Based on the pedagogy of Paulo Freire and participatory development paradigms these are rooted in the mass democratic struggles against apartheid. This paper is based on extensive research by the authors as participant observers and activists, conducted over many years into university-based adult education on the one hand, and praxis outside academic institutions, on the other. The authors have a his- tory of engagement in worker education, and key elements of education in the non-racial trade union move- ment as one of the most important organised forces of internal political resistance are suggested as informing curricula of university-based adult education. Since 1994 and the change to democracy, adult education departments in universities have increasingly been eroded or disappeared as separate departments or programmes. Like elsewhere in the north, we have witnessed the undermining and increased professionalization and institutionalization of adult education across contexts – and with it a marked reduction in radical outlook and purpose. However, the method- ological approach has remained committed to participation and dialogue, and, with the waning of commu- nity-based students who bring with them extensive experience from the field, there is a consistent emphasis on other, practice-based knowledges through guest educators, and by sending students to design and con- duct research and small interventions, at community level. Popular education outside the university takes numerous forms, and as an 18-month research project has shown, there are still many initiatives that target members of working class communities who have no other access to education. Much of this work is based on a ‘pedagogy  of contingency’ in that it responds di rectly to local needs and concerns. However, not all of the popular education practices continue the tradi tion of radical, conscientising education. We describe three tensions or contradictions experienced by ed- ucators concerned with transformation; firstly, the tension between participation as a principle or a technique; secondly, the tension between individual or collective change; thirdly, the tension between working ‘bottom- up’ or ‘top-down’ in designing curricula and asking ‘Who leads, and who follows?’ in attempts to work dem- ocratically. We conclude that constraints and demands informed by neoliberal politics have made the work of activist academics and academic activists increasingly difficult. The paper concludes by suggesting that building global solidarity amongst adult educators who have carried their struggles from the past into the future, and younger educators who create new forms of radical pedagogy forward, are important ways of keeping social justice agendas and practices alive.